Implementing an Integrated Learning Model (Blegur Model) to Enhance Students' Critical Academic Writing, Digital Literacy, and Autonomous Learning - Zuvyati Aryani Tlonaen; Christin Prima Mery Rajagukguk; Zet Ena; Jusuf Blegur (Universitas Lambung Mangkurat, 2026)
This study examines the improvements in students' critical academic writing skills, digital literacy, and autonomous learning through the implementation of an integrated learning model (Blegur model). This study adopted a mixed-methods explanatory sequential design. Quantitative data (pretest-posttest) from 32 students were collected using standardized instruments: the Fundamentals of Academic Writing Rubric (20 items), the Students' Digital Competence Scale (SDiCoS, 28 items), and the Autonomous Learning Scale (ALS, 12 items). The quantitative data were analyzed using paired-samples t-tests. The intervention was implemented over one semester through eight structured learning syntaxes (orientation, distribution, experimental, presentation, analysis, problem solving, competition, and award). Additional qualitative data were obtained through in-depth interviews, which were analyzed thematically to validate the findings. The quantitative results showed highly significant improvements in all three variables (p <0.001). Critical writing skills improved across all indicators, followed by improvements in six digital literacy indicators and aspects of autonomous learning. Qualitative findings revealed five themes that support the quantitative results, reflecting shifts in students’ writing, digital literacy, learning independence, critical thinking, and academic self-confidence. Therefore, both quantitative and qualitative analyses indicated that the integrated model improves students’ critical academic writing, digital literacy, and autonomous learning. Four factors influenced the improvements: active engagements in the learning process, exposure to and use of academic technology, clear and directed learning structure, and collaborative practices. Thus, this integrated learning model has proven effective and is recommended for courses that emphasize critical thinking skills, digital literacy, and autonomous learning.